Synthesis, docking study and neuroprotective effects of some novel pyrano[3, 2-c]chromene derivatives bearing morpholine/phenylpiperazine moiety. Issue 15 (1st August 2017) - Sameem, Bilqees; Saeedi, Mina; Mahdavi, Mohammad; Nadri, Hamid; Moghadam, Farshad Homayouni; Edraki, Najmeh; Khan, Muhammad Imran; Amini, Mohsen
Graphical abstract: Highlights: Novel pyrano [3, 2- c ]chromens were synthesized and evaluated for their anti-AChE/BuChE activity. Molecular docking studies provided insights into enzyme-inhibitor interactions. One of the most active compounds, 6c showed neuroprotective effect against H2 O2 -induced cell death in PC12 neurons. The BACE-1 inhibitory activity of6c was evaluated by fluorescence resonance emission transfer method. The kinetic mode of interaction of the most potent compound6c confirmed mixed inhibitory activity. Abstract: Novel pyrano[3, 2- c ]chromene derivatives bearing morpholine/phenylpiperazine moiety were synthesized and evaluated against acetylcholinestrase (AChE) and butylcholinestrase (BuChE). Among the synthesized compounds, N -(3-cyano-4-(4-methoxyphenyl)-5-oxo-4, 5-dihydropyrano[3, 2- c ]chromen-2-yl)-2-(4-phenylpiperazin-1-yl)acetamide (6c ) exhibited the highest acetylcholinestrase inhibitory (AChEI) activity (IC50 = 1.12 µM) and most of them showed moderate butylcholinestrase inhibitory activity (BChEI). Kinetic study of compound6c confirmed mixed type of inhibition towards AChE which was in covenant with the results obtained from docking study. Also, it was evaluated against β -secretase which demonstrated low activity (inhibition percentage: 18%). It should be noted that compounds6c, 7b, 6g, and7d showed significant neuroprotective effects against H2 O2 -induced PC12 oxidative stress.